PP.LB01.04: A NEW METHOD TO MEASURE THE SHORT TERM BLOOD PRESSURE VARIABILITY. (June 2015) - Strocchi, E.; Greco, T.; Malini, P.L.; Rosticci, M.; Rinaldi, E.R.; Borghi, C.
Abstract : Objective: Beside the well-known evidences of the additional cardiovascular risk linked to a chronic increase of the pressure values, it is also likely that their variability may play a role as a risk factor. The blood pressure variability (BPV) is usually estimated using the Standard Deviation (SD) from the mean; our study allowed to elaborate a new method to assess the BPV as the average of the absolute difference between subsequent blood pressure measures; this method of calculating BPV was applied to the BP values measured routinely with standard ambulatory blood pressure monitoring (ABPM). Design and method: The ABPM data gathered by means of the Spacelab devices were used to calculate the BPV and the BPV% (corrected by average blood pressure values) for each patient. The BPV% was calculated for daytime and nightime separately and the range of BPV% was compared with the range of SD for the entire group of patients and the relation of BPV% with other common variables such as age and sex, normal or above normal blood pressure and Dippers or Non Dippers conditions, was analysed.. Results: 196 ABPMs of male and female patients have been examined; average age = 59 years (38% of the ABPM were obtained in patients > 65 yrs); in 23% of the cases the average blood pressure values measured by ABPM was above normal. The average BPV% taken during the day, for the entire group of the examined patients, was 6, 8%, 9% and 8, 1 % respectively for SBP, DBP and MBP; BPV% during nightime was excluded for methodollogical reasons (limited number of measures and overlap with values obtaine while awake). Comparisons between the subgroups has shown an increased variability for the women, the elders and the Non Dippers. Conclusions: The BPV% is only partially related to the SD (which is more commonly used as variability index) and could be more informative; it is easy to perform and if its usefulness and reliability will be confirmed, it could even be used routinely for the evaluation of ABPM.